(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
As a young man, Eliot in his early criticism tends to miss the mark of deconstruction, but since he is aware of the dialectic of the past and present, he soon gets back to the path of equivocation. For instance, in the essay ’ Tradition and the Individual Talent’, he gives the impression as if tradition is prior, more significant than the individual. In fact he says Tradition is a matter of wider significance. It cannot be inherited and if you want it you must obtain it by great labour. 6Similarly, he says No poet, no artist of any art, has his complete meaning alone. His significance, Ms appreciation is the appreciation of his relation to the dead poets and artists. You cannot value him alone, you must set him, for comparison and contrast among the dead. 7 But soon, afterwards, he also says The necessity that he shall conform, that he shall cohere is not one-sided what happens when a new work of art is created is something that happens simultaneously to all the works of art which preceded it.8